MANAJEMEN PERMODALAN UNTUK MENINGKATKAN KESEHATAN BMT MASLAHAH NGAWI - Adella, Salma Nauval; Rizal, Fitra (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2024)
This research is based on the world of sharia banking business in this modern era. BMT Maslahah Ngawi Branch's efforts to maintain health through capital management originating from owners, shareholders and several operational income results based on certain provisions. The aim of this research is to analyze capital management, health level, obstacles faced by BMT Maslahah Ngawi Branch. The formulation of the research problem is 1) What is the health level of BMT Maslahah Ngawi Branch, 2) How is the capital management of BMT Maslahah Ngawi Branch, 3) What are the obstacles faced by BMT Maslahah Ngawi Branch in improving health. This research is field research and uses a descriptive qualitative approach through in-depth interviews, field observations and documentation of BMT Maslahah Ngawi Branch by staff and managers, analyzed using an inductive method in the form of specific data categorized as data reduction, display data and ends with data verification. The results of the research on BMT Maslahah Ngawi Branch can be concluded that: 1) The health level of BMT Maslahah Ngawi Branch in 2019-2022 experienced a percentage decrease, showing a CAR of 6.30%, occupying the title of Less Healthy. 2) Capital Management through marketing techniques and empowering human resources. 3) The problem with BMT Maslahah Ngawi Branch is that the management is considered unprofessional, and the lack of customer responsibility has an impact on customer financing obligations.